Estimating the Differential Mode Noise of a DC-DC Converter - Yoppy Yoppy; Dwi Mandaris; Aditia Nur Bakti; Hutomo Wahyu Nugroho; Yudhistira Yudhistira; Deny Hamdani (National Research and Innovation Agency, 2023)
Electromagnetic noise emission is inevitable in a DC-DC converter due to the employed switching technique. In low frequency, the noise propagating through cabling and conductive media is called a conducted emission. A conducted emission consists of differential mode and common mode noise. It is advantageous to know an estimate of emission level for each mode during the design phase so that suitable mitigation can be included earlier.. This paper aims to focus on a method to estimate the differential mode noise emission of a DC-DC converter. The estimation is computed using the input capacitor complex impedance and the current that flows through it. As a study case, a boost and buck converters are used for evaluation. The estimation and measurement results are compared. Despite differences at some frequencies, the estimated and measured results generally agree well. Because of its simplicity, the proposed method can be used as a practical tool in the EMC aspect of DC-DC converter design.